2017
DOI: 10.2147/ijn.s141052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synergistic osteogenesis between icariin and BMP2 through a micro/meso hierarchical porous delivery system

Abstract: BMP2 is well known as an outstanding growth factor for inducing new bone formation. However, improvements are still required to use BMP2 effectively and expand its clinical application due to the potential side effects at high doses. In this study, icariin (IC), a type of traditional Chinese medicine, was originally proposed to be a cooperative factor for BMP2. An alkaline phosphatase (ALP) activity assay showed that IC promoted BMP2 osteogenesis in a concentration-dependent manner with significant enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…BMPs are prominent growth factors that induce new bone formation [62]. BMP-2 is a member of the BMP family and enhances the migration and proliferation of HVSMCs via the actin/CD44/MMP-2 molecular pathway [63].…”
Section: Bone Morphogenetic Protein-2mentioning
confidence: 99%
“…BMPs are prominent growth factors that induce new bone formation [62]. BMP-2 is a member of the BMP family and enhances the migration and proliferation of HVSMCs via the actin/CD44/MMP-2 molecular pathway [63].…”
Section: Bone Morphogenetic Protein-2mentioning
confidence: 99%
“…Arising studies have demonstrated that icarrin play a vital role in regulating these genes. Wang et al used ALP activity assay to observe that icariin stimulate BMP2 osteogenesis in a concentration-dependent manner ( 29 ). Besides, the expression of osteogenic genes (Col I, Runx2, osteopotin and DLX5) were significantly elevated by icariin in rat bone marrow stromal cells ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Conditions such as trauma, tumors, and inflammation will impair the structure and functions of bone, thus resulting in bone defects that, in turn, significantly impact psychological health and the quality of life. 5 To overcome the limitations of traditional bone grafting, tissue engineering has become the strategy with the most potential for the clinical treatment of bone defects. 6 Tissue engineering approaches are mainly based on the use of scaffolding biomaterials, seed cells and growth factors/molecules.…”
Section: Introductionmentioning
confidence: 99%